2020
DOI: 10.1161/jaha.120.017477
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelial Nitric Oxide Synthase in Isoflurane Conditioning‐Induced Neurovascular Protection in Subarachnoid Hemorrhage

Abstract: Background Delayed cerebral ischemia remains a common and profound risk factor for poor outcome after subarachnoid hemorrhage (SAH). The aim of our current study is to define the role of endothelial nitric oxide synthase (eNOS) in isoflurane conditioning‐induced neurovascular protection after SAH. Methods and Results Ten‐ to 14‐week‐old male wild‐type mice (C57BL/6) as controls and eNOS knockout male mice (strain # 002684) were obtained for the study. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 16 publications
1
40
0
1
Order By: Relevance
“…Our data also show that brief exposure to 2% isoflurane beginning one hour after SAH induction protects against one key element of DCI-large artery vasospasm, which is consistent with our past results [15]. In addition, we show that isoflurane conditioning protects against another critical component of DCI-microvessel thrombosis.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our data also show that brief exposure to 2% isoflurane beginning one hour after SAH induction protects against one key element of DCI-large artery vasospasm, which is consistent with our past results [15]. In addition, we show that isoflurane conditioning protects against another critical component of DCI-microvessel thrombosis.…”
Section: Discussionsupporting
confidence: 93%
“…This protection was casually linked to endothelial cell-derived HIF-1α [14]. More recently, we have shown that isoflurane conditioning provides strong protection against vasospasminduced DCI and neurological deficits in a mouse model of SAH [15,39] and that this protection is critically dependent on eNOS [15].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations